Corneal Cross-Linking in a 4-Year-Old Child With Keratoconus and Down Syndrome. Issue 9 (September 2015) - Sabti, Saad; Tappeiner, Christoph; Frueh, Beatrice E.
Abstract : Purpose: To describe the clinical outcome of corneal cross-linking (CXL) in a young child with keratoconus. Methods: This is a case report of a young girl with keratoconus with ophthalmologic findings and 3-year follow-up. Follow-up visits included visual acuity measurement, retinoscopy, corneal tomography, and topography. Results: A girl with Down syndrome was diagnosed with bilateral keratoconus and relative amblyopia at the age of 4 years. The best-corrected near visual acuity was 20/100 binocularly. Corneal tomography showed the following parameters: OD Kmax 47.2 diopters (D), thinnest location 442 μm; OS Kmax 49.6 D, thinnest location 432 μm. Three months later, the keratoconus in the left eye progressed (Kmax 50.2 D, thinnest location 424 μm), and CXL was performed. One year later, CXL was necessary also in the right eye because of progression. The girl was most recently reexamined at the age of 7 years. The corrected near visual acuity was 20/80 in both eyes. The corneal curvature slightly flattened, and the corneal thickness stabilized (OD Kmax 46.8 D, thinnest location 389 μm; OS Kmax 49.4 D, thinnest location 360 μm). Conclusions: Onset of keratoconus can occur in early childhood, especially in patients with Down syndrome. In this case, CXL was performed at 4 and 5 years of age without complications and stopped further keratoconus progression.